1995
DOI: 10.1136/jmg.32.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Deletion patterns of Duchenne and Becker muscular dystrophies in Greece.

Abstract: We present molecular data from 90 Greek boys with Duchenne or Becker muscular dystrophy using cDNA analysis or mVltiplex PCR or both. Deletions were detected in 63*3% ofpatients and were mainly clustered in two areas of the gene, one in the 3' and one in the 5' end of the gene (exons 3-19 and 44-53

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

1995
1995
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 16 publications
2
12
0
1
Order By: Relevance
“…In Turkish DMD patients, deletions were found in 52–59% DMD patients [19, 20]. In Greece, deletions were detected by PCR in 63% cases [21]. The lowest rate of deletion mutations in DMD patients has been reported from the Philippines (33% [22]) and Israel (37% [23]).…”
Section: Discussionmentioning
confidence: 99%
“…In Turkish DMD patients, deletions were found in 52–59% DMD patients [19, 20]. In Greece, deletions were detected by PCR in 63% cases [21]. The lowest rate of deletion mutations in DMD patients has been reported from the Philippines (33% [22]) and Israel (37% [23]).…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, a marked difference, since we report a low percentage of recombination between STR44 and STR50, which is a "hot spot" of deletions for our DMD/BMD patients. However, as we have previously reported (Florentin et al 1995), the distribution of deletions in this region is different in our sample and the major breakpoint "hot spot" observed in Greek DMD/BMD patients is in intron 50. Therefore, the differences observed in the current study could be attributed to the role played by the "local DNA environment" in the creation of deletions (Krawczak and Cooper 1991;Cooper and Krawczak 1991 ) and in homologous and nonhomologous recombination (Ruley and Fried 1983;Nicholls et al 1987;Yen et al 1990).…”
Section: Discussionmentioning
confidence: 39%
“…All patients were screened with cDNA probes and/or multiplex polymerase chain reaction (PCR) (Abbs et al 1991) for 18 exons of the DMD gene; deletions were detected in 65% of them (Florentin et al 1995). Families were chosen randomly when they were referred to the Genetics Unit; they came from all parts of Greece.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies in the Greek population have also described differences in deletion breakpoints and in recombination events in the STR 44-50 region of the dystrophin gene. 32,33 Moreover, the incidence of the polymorphism C to T at position + 15 of intron 66, in Greek population, is found with a frequency of 15% which is greater than the 5% frequency reported by Lenk et al 15 The three frameshift products that were revealed by cDNA analysis in patient D286 demonstrate the usage of the alternative splicing mechanism. This property of the carboxy terminus of the gene is also evident in the case of BMD patient D320 in whom the DNA defect on exon 74 activates exon skipping and finally restores the frameshift mutation.…”
Section: Discussionmentioning
confidence: 82%